A ReaxFF-based molecular dynamics study of the pyrolysis mechanism of polyimide. (April 2015) - Lu, Xu; Wang, Xuelei; Li, Qingmin; Huang, Xuwei; Han, Shuai; Wang, Gaoyong
Abstract: Reactive Force Field (ReaxFF) molecular dynamics simulation is first employed in Kapton-type polyimide pyrolysis process. A series of ReaxFF simulations are carried out to study the pyrolysis mechanisms of polyimide. The effects of temperature on the distribution of various products are investigated. Carbon dioxide and cyano radical are the dominant products, and a large number of acetylene molecules are first discovered at high temperature. Other small molecular products including water, carbon monoxide and hydrogen are detected in the ultimate products as well. Formation mechanisms of dominant products (CO2 and CN) are discussed in detail for the first time based on the simulation trajectories. The cleavage of C–N bond on the imide ring is the common initial step for forming CO2 and CN. The structure (–C(=O)–O–C–) is important and conducive for generating CO2, whereas the consecutive dissociation of C–N on the imide ring and the de-carbonization reaction from the benzene are integral for forming CN. The apparent activation energy and pre-exponential factor for pyrolysis of polyimide extracted from the ReaxFF simulations are well consistent with experimental results. The present work demonstrates that ReaxFF simulation is a promising method to elucidate detailed chemical reaction mechanisms in polymer pyrolysis. Highlights: Carbon dioxide and cyan are found to be dominant products of polyimide pyrolysis. The initial step to form CO2 is C–N bond cleavage on imide ring. It turns compulsory in the second step. Pathway includes C–N dissociation and benzene de-carbonization with characteristic cyclopentadiene. Quantitative difference between CO2 and CN lies in the amount of broken C–N bonds on the imide ring.